Enterobiasis in Ectopic Locations Mimicking Tumor-Like Lesions - Silvio Pampiglione; Francesco Rivasi (International Journal of Microbiology)
Both the clinical and the histopathological diagnostic difficulties of oxyuriasis in unusual sites and their importance from a clinical point of view are pointed out. The authors report two ectoptic cases of enterobiasis observed in Northern Italy, one located in a fallopian tube of a 57-year-old woman and the other in a perianal subcutaneous tissue of a 59-year-old man, mimicking tumor-like lesions. The authors take advantage of the occasion to focus the attention of the medical world on this subject, lamenting the scarce importance given to this parasitosis in university courses of medical schools and in medical textbooks as it is incorrectly considered “out-of-fashion.”